Individual Factors as Predictors of Extension Agents’ Performance in the Mekong Delta, Vietnam - Le, Ngoc Thach (2008)
Extension agents are important human resources in community development. They link agencies and community in the process of knowledge and technology transfer particularly to rural communities. In a developing country such as Vietnam, research on performance and factors that affect extension agents’ performance in extension service system are lacking. However, these researches are important, considering the fact that the country is fast moving into agro-based industries. The purpose of this study is to explore the individual factors that influence extension agents' performance. The study is guided by the following research questions: (1) What is the level of performance in extension as perceived by the extension agents? (2) What is the level of predicting variables of extension agents? (3) Are there differences in extension skills and performance between the provincial and district extension agents? (4) What is the relationship between the individual factors and extension agents' performance? (5) What factors most influence extension agents' performance? The individual factors are motivation, skill as instructional designer and communicator, skill as facilitator, teaching skill, program planning skill, program implementation skill, program evaluation skill, social skill ability, external contact ability, and professional profile of the extension agents. These factors are the independent variables for this research. Work performance consists of variables such as quality of work, dependability, work schedule, work habit, work allocation, poise and composer, work organization, and customer satisfaction all of which are treated as the dependent variables. A sample of 369 agriculture extension agents from seven provincial/city extension centers were selected randomly from a total population of 649 extension agents who came from the 13 provinces/city of the Mekong Delta. Data collection was conducted from December 2006 and to February 2007. Multiple Linear Regression and Independent-Samples t-test were used to analyze the data from a sample of 312 respondents. The extension agents rated their performance at a high level. The study exposes four individual factors that significantly contributed to performance of extension agents, namely, social skills, program implementation skills, motivation, and program planning skills. The study also reveals four types of skills that are significantly different between the two groups of agriculture extension professionals. These skills are skill as instructional designer and communicator, skill as facilitator, program planning skill, and external contact ability. The knowledge generated from this study is useful for extension agencies in developing training program for their extension agents. It is suggested that future research should replicate this study to extension agents in the other areas such as forestry, environmental and natural resources as well as agro-tourism. The influence of technical skills on the job performance of extension agents is another possible research worth researching.